Competition and specialization in an African forest carnivore community. Issue 18 (27th August 2019) - Mills, David R.; Do Linh San, Emmanuel; Robinson, Hugh; Isoke, Sam; Slotow, Rob; Hunter, Luke
Abstract: Globally, human activities have led to the impoverishment of species assemblages and the disruption of ecosystem function. Determining whether this poses a threat to future ecosystem stability necessitates a thorough understanding of mechanisms underpinning community assembly and niche selection. Here, we tested for niche segregation within an African small carnivore community in Kibale National Park, Uganda. We used occupancy modeling based on systematic camera trap surveys and fine‐scale habitat measures, to identify opposing preferences between closely related species (cats, genets, and mongooses). We modeled diel activity patterns using kernel density functions and calculated the overlap of activity periods between related species. We also used co‐occupancy modeling and activity overlap analyses to test whether African golden cats Caracal aurata influenced the smaller carnivores along the spatial and/or temporal axes. There was some evidence that related species segregated habitat and activity patterns. Specialization was particularly strong among forest species. The cats and genets partitioned habitat, while the mongooses partitioned both habitat and activity period. We found little evidence for interference competition between African golden cats and other small carnivores, although weak interference competition was suggested by lower detection probabilities of some species at stations where African golden cats were present. This suggests that community assembly and coexistence in this ecosystem are primarily driven by more complex processes. The studied carnivore community contains several forest specialists, which are typically more prone to localized extinction. Preserving the observed community assemblage will therefore require the maintenance of a large variety of habitats, with a particular focus on those required by the more specialized carnivores. Abstract : In African forests where leopards have been extirpated, the remaining carnivore community is structured by habitat preference rather than interference competition. This means that the African golden cat, the largest remaining carnivore in these communities, will not suppress populations of smaller carnivores, as has been observed in other communities where mesopredator release causes dramatic restructuring throughout communities of carnivores and their prey. Protection of forest habitat will therefore preserve the remaining forest carnivore community assembly.